2011
DOI: 10.1007/s10725-011-9622-x
|View full text |Cite
|
Sign up to set email alerts
|

New basal media for half-anther culture of Anthurium andreanum Linden ex André cv. Tropical

Abstract: A successful protocol for high frequency callus induction and plant regeneration from Anthurium andreanum Linden ex André cv. Tropical half-anthers is described. Different variables using Winarto and Teixeira and Murashige and Skoog basal media supplemented with several plant growth regulators [2,4-dichlorophenoxy acetic acid (0.1-1.0 mg/l), a-naphthalene acetic acid (0.01-0.2 mg/l), thidiazuron (0.5-2.0 mg/l), 6-benzylaminopurine (0.5-1.0 mg/l), and kinetin (0.5-1.0 mg/l)] were tested for their ability to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
0
8
0
5
Order By: Relevance
“…In preliminary studies, induction and regeneration of callus followed by shoot and root regeneration are the main steps of tissue culture of whole plants. As an important commercial plant, to develop a rapid and more effective tissue culture protocol to shorten the time is the main objective of Anthurium tissue culture [7,10,22,23].…”
Section: A Species Explant Source Sterilization Methods Referencementioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies, induction and regeneration of callus followed by shoot and root regeneration are the main steps of tissue culture of whole plants. As an important commercial plant, to develop a rapid and more effective tissue culture protocol to shorten the time is the main objective of Anthurium tissue culture [7,10,22,23].…”
Section: A Species Explant Source Sterilization Methods Referencementioning
confidence: 99%
“…is Benlate], Cetrimite, gentamicin and streptomycin sulphate are effectively used for this aim [11,13,15,18,20,22]. Each plant species has its own medium composition or it should be improved for better results.…”
Section: Establishing Aseptic Culturementioning
confidence: 99%
“…Mata tunas dan daun dipotong berbentuk kubus (0,5-1,00 cm) dan dikultur pada media Winarto-Teixeira (WT) (Winarto et al 2011) yang mengandung 2 mg/l TDZ, 0,5 mg/l BA, dan 0,02 mg/l NAA baik cair maupun padat. Tunas baru terbentuk ± 2 bulan setelah kultur dan selanjutnya dipanen daunnya sebagai sumber eksplan.…”
Section: Sterilisasi Dan Isolasi Eksplanunclassified
“…All media were adjusted to pH 5.3 with 1 N NaOH or HCL prior to autoclaving at 100 KPa for 17 min. Cultures were kept on 40 ml medium in 100 ml Two new PLB-induction media, Teixeira Cymbidium (TC) medium, TC-1 and TC-2, inspired by but different to Winarto-Teixeira (WT) medium for Anthurium (Winarto et al, 2011), were tested against the industry standards, VW and half-strength MS (Tab. 1).…”
Section: Plant Materials and Culture Conditionsmentioning
confidence: 99%
“…Namely, VW medium and similar media with weak concentrations of macro-and micro-nutrients (TC-1 or TC PLB in this study), were necessary for PLB induction and formation while higher levels of these nutrients were required for callus formation, namely MS, 1/2MS and TC-2 (i.e., TC CALLUS ). Winarto et al (2011) developed, though extensive media testing, a new medium, Winarto-Teixeira (WT) medium, for Anthurium. Several studies, including this study, have indicated that basal medium is key to the success of a tissue culture protocol.…”
Section: Statistical Analysesmentioning
confidence: 99%